The allocation of German aid: self-interest and government ideology - Dreher, Axel; Nunnenkamp, Peter; Schmaljohann, Maya (Economics & politics, 2015)
We investigate the importance of geo-strategic and commercial motives for the allocation of German aid to 138 countries over the 1973-2010 period. We find that geo-strategic and commercial motives matter. When we relate them to the political color of the German government in general, and the Ministry for Economic Cooperation and Development and the Federal Foreign Office in particular, we find their importance to be at least as strong under the socialist leadership. Socialist leadership decreases the amount of aid commitments, controlled for other factors.
Gesehen am 29.06.2020